Survival rates of different Penaeus monodon Fabricius postlarval stages - Primavera, J. H. (1976)
The objective of this study is to determine survival rates of different postlarval stages upon stocking in the Leganes ponds. Twelve 3m x 2m x 2m suspension nets made of nylon cloth (mesh size = 0.1 mm) were set up in a Leganes Station pond (ave. water depth = 1 m) by means of 3-m long poles stacked at distances approximating the area of each net. The net bottom was filled with topsoil at least 15 cm thick to stimulate the pond bottom. At least 60 cm of the upper edge of each net was above the water level to prevent mixing of water inside and outside the net. P. monodon of stages P11, P15, P21 (from the hatchery) and P25 (from the wet lab) were stocked in the nets at 200/sq m or 1,200 fry/net. Due to lack of fry, only one P25 net was stocked. Each net had two large dried miapi branches as shelter from predation and cannibalism for the young sugpo fry. Fresh lablab was fed at the rate of one pail (approximately 5 kg) every four days per net. Harvest data show relatively higher survival rates for P15 and P18 compared to P11 and P25 with no significant difference between these two stages. The results for P25 may not be valid because the stock came from the wet lab in comparison to the other postlarval stages which were reared in the hatchery. Moreover, the P25 stock had no replicates and the net itself (no. 10) was discovered to have many holes. These preliminary results point to P15 as the best stage for harvest from the hatchery in terms of high pond recovery and lesser expense in rearing compared to older postlarvae.